Field Monitoring of Treated Industrial Waste Water - Vasudha Bhandari; Preeti Abrol (Institute of Advanced Engineering and Science, 2013)
Discharge of untreated industrial water on land and in existing waterbodies has deteriorated the quality of these sources and has become harmful and disasterous for human as well as aquatic life..Many a times even treated industrial effluents are proved to be harmful. So in the project discussed below an effort has been made to test the treated industrial waste water and send the obtained results to the concerned industry as well as pollution control board. The sensor used to test the water were pH electrode (PE03), conductivity electrode (k=1), purity sensor, thermistor. The results obtained from the above sensors were then sent to the industry control room as well as pollution control board.using GSM.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3177